NERICA dissemination project in West Africa - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project engages farm families in participatory varietal selection (PVS) strategy to accelerate NERICA dissemination. The objective of the project is to help small-scale producers in the seven pilot countries to improve rice production and incomes through the dissemination of NERICA and other improved varieties and complementary technology. About 80% of the targeted beneficiaries of the project are the rural poor, mostly women.